Low-temperature reaction type hot melt adhesive tape and preparation method thereof

The thermoplastic polyurethane is prepared by using a low-temperature reactive formula in the hot melt tape, including the reaction of mixed polyols and diisocyanate, which solves the problem of poor useability of hot melt adhesives in low temperature environments, achieves efficient bonding and film formation, and expands the application range.

CN119799259APending Publication Date: 2025-04-11江苏伊诺尔新材料科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510078155.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing hot melt tape is poorly used in low temperature environments, which can easily cause damage and deformation of temperature-sensitive materials, limiting its application range.

Method used

Low-temperature reactive hot melt tape is used, and its formula includes 65-85 parts of mixed polyol, 7-18 parts of diisocyanate, 2-5 parts of antioxidant, 2-5 parts of tackifying resin, 1.3-2.7 parts of toughening agent and 0.1-0.4 parts of defoaming agent. Thermoplastic polyurethane is prepared by reacting the mixed polyol with diisocyanate, which improves the adhesive ability and film forming properties.

Benefits of technology

It realizes softening and bonding of hot melt adhesive at low temperature, improves the bonding strength and flexibility of the adhesive film, and expands its application range.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of hot melt adhesives, and particularly discloses a low-temperature reaction type hot melt adhesive tape. The low-temperature reaction type hot melt adhesive tape is prepared from the following raw materials in parts by weight: 65 to 85 parts of mixed polyol, 7 to 18 parts of diisocyanate, 2 to 5 parts of an antioxidant, 2 to 5 parts of tackifying resin, 1.3 to 2.7 parts of a toughening agent and 0.1 to 0.4 part of a de-foaming agent, wherein the mixed polyol comprises polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran glycol; in addition, the preparation method disclosed by the invention has the advantage of improving the usability of the hot melt adhesive in a low-temperature environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of hot melt adhesives, and more specifically, to a low-temperature reactive hot melt adhesive tape and a preparation method thereof. Background Art

[0002] Hot melt tape is a kind of adhesive material. It is solid at room temperature and is easy to store and transport. When used, it needs to be heated to soften it and then covered on the bonding surface. After its temperature drops, it will re-solidify and fix the bonding surface. It has good bonding effect and bonding strength.

[0003] Currently, most of the existing hot melt tapes are made of ethylene-vinyl acetate copolymer and polyolefin raw materials. Since the hot melt adhesive needs to be heated and softened to have sufficient bonding ability, the operating temperature of the hot melt adhesive is generally high. However, for the bonding of temperature-sensitive materials, the use of hot melt adhesive is greatly restricted and it is easy to cause material damage and deformation, limiting its scope of application. Summary of the invention

[0004] In order to improve the usability of hot melt adhesive in low temperature environments, the present application provides a low-temperature reactive hot melt adhesive tape and a preparation method thereof.

[0005] In the first aspect, the present application provides a low-temperature reactive hot-melt adhesive tape, which adopts the following technical solution: A low-temperature reactive hot-melt adhesive tape comprises the following raw materials in parts by weight: 65-85 parts of mixed polyols, 7-18 parts of diisocyanates, 2-5 parts of antioxidants, 2-5 parts of tackifying resins, 1.3-2.7 parts of toughening agents, and 0.1-0.4 parts of defoaming agents, wherein the mixed polyols comprise polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200, and polytetramethylene glycol.

[0006] By adopting the above technical scheme, a mixed polyol reacts with a diisocyanate to obtain a thermoplastic polyurethane, which can be softened when heated, and the bonding ability is greatly improved. The tackifying resin still has good fluidity at low temperatures, and can improve the fluidity of the hot melt adhesive after softening, so that the hot melt adhesive can cover the bonding surface easily. The polytetrahydrofuran diol destroys the regularity of polyethylene glycol, so that the polyol formed by the composite of polyethylene glycol and polytetrahydrofuran diol has a lower softening point. The composite of polyethylene glycols with different molecular weights can improve the film-forming property of the hot melt adhesive. The toughening agent can effectively improve the strength of the adhesive film formed by the curing of the hot melt adhesive, improve its flexibility and breaking strength, and thus improve the bonding strength.

[0007] Preferably, in the mixed polyol, the mass ratio of polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol is (0.28-0.32):(0.27-0.33):(0.23-0.26):(2.82-3.16).

[0008] By adopting the above technical solution and controlling the addition amount of polyethylene glycol with different molecular weights, polyethylene glycol with different molecular weights can be entangled and connected with each other, so that a good strength adhesive film is formed after the hot melt adhesive is cured. Polytetrahydrofuran diol contains easily rotatable ether oxygen bonds, which introduce soft segments into the adhesive film. Too low an addition amount will affect the flexibility of the adhesive film, and too high an addition amount will easily affect the formability and strength of the adhesive film.

[0009] Preferably, the toughening agent is polyacrylonitrile porous hollow fiber and nanocellulose whisker.

[0010] By adopting the above technical scheme, the polyacrylonitrile porous hollow fiber has a hollow structure and good mechanical properties, which can effectively improve the tensile strength of the film, thereby helping to improve the flexibility of the film. The nanocellulose whiskers have high strength and are entangled and overlapped with the polyacrylonitrile porous hollow fiber, which can further improve the flexibility of the film.

[0011] Preferably, the mass ratio of the polyacrylonitrile porous hollow fiber to the nanocellulose whiskers is (1.25-1.67):(0.67-0.98).

[0012] By adopting the above technical solution, the mass ratio of polyacrylonitrile porous hollow fibers and nanocellulose whiskers is controlled to achieve the best synergistic effect between the two, thereby improving the tensile strength and mechanical properties of the film.

[0013] Preferably, the method for preparing the polyacrylonitrile porous hollow fiber comprises the following steps: dissolving polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide to form a shell spinning solution, dissolving polyvinyl pyrrolidone in N,N-dimethylformamide to form a core spinning solution, coaxially electrospinning the core spinning solution and the shell spinning solution to obtain a composite fiber, heating the composite fiber at 55-60°C for 12-13h, placing it in water, and shaking it at 55-60°C for 3-4h.

[0014] By adopting the above technical scheme, the shell layer spinning solution and the core layer spinning solution are coaxially electrospun to form a composite fiber with a shell-core structure. After the composite fiber is heated, the non-volatile solvent is removed, and polyvinyl pyrrolidone is precipitated by shaking in water to obtain a polyacrylonitrile porous hollow fiber.

[0015] Preferably, graphene is also added to the shell spinning solution, and the added amount of graphene is 0.89-1.16wt% of the polyacrylonitrile.

[0016] By adopting the above technical solution, graphene is added to the shell spinning solution, so that graphene is incorporated into the polyacrylonitrile porous hollow fiber. Graphene has good mechanical properties and strength and can effectively improve the tensile strength of the polyacrylonitrile porous hollow fiber.

[0017] Preferably, the nanocellulose whiskers are treated as follows: the nanocellulose whiskers are dispersed in glacial acetic acid to form a suspension, a mixture of sulfuric acid, glacial acetic acid and acetic anhydride is added dropwise while stirring, the temperature is raised to 40-45° C. after the addition, the reaction is carried out for 30-35 minutes, the nanocellulose whiskers are washed with ethanol and acetone, and the suspension is filtered.

[0018] By adopting the above technical solution, the nanocellulose whiskers can improve their dispersibility in the raw material after being treated with acetate, so that they are evenly dispersed with the polyacrylonitrile porous hollow fibers and the strength of the film is enhanced.

[0019] In a second aspect, the present application provides a method for preparing a low-temperature reactive hot-melt adhesive tape, using the following technical solution: A preparation method of a low-temperature reactive hot-melt adhesive tape comprises the following steps: stirring and mixing polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol to obtain a mixed polyol; mixing the mixed polyol, a tackifying resin, an antioxidant and a defoaming agent, and vacuum dehydrating the mixture at 100-130°C for 1.5-2h; adding a toughening agent to the mixture, stirring and dispersing the mixture at a speed of 1500-3200r / min and a temperature of 120-145°C for 1-2h, adding diisocyanate, maintaining the reaction temperature at 120-135°C, stirring for 2-3h, extruding and molding, and cooling to obtain a low-temperature reactive hot-melt adhesive tape.

[0020] By adopting the above technical scheme, the mixed polyol and diisocyanate are mixed and cross-linked to obtain thermoplastic polyurethane, thereby obtaining a hot melt adhesive tape with a low softening point and high adhesive film strength after curing.

[0021] In summary, this application has the following beneficial effects: 1. In the present application, the mixed polyol reacts with the diisocyanate to obtain a thermoplastic polyurethane, which can be softened by heating, and the bonding ability is greatly improved. The tackifying resin still has good fluidity at low temperatures, which can improve the fluidity of the hot melt adhesive after softening, making it easier for the hot melt adhesive to cover the bonding surface. The polytetrahydrofuran diol destroys the regularity of the polyethylene glycol, so that the polyol formed by the composite of polyethylene glycol and polytetrahydrofuran diol has a lower softening point. The composite of polyethylene glycols of different molecular weights can improve the film-forming property of the hot melt adhesive. The toughening agent can effectively improve the strength of the adhesive film formed by the curing of the hot melt adhesive, improve its flexibility and fracture strength, and thus improve the bonding strength.

[0022] 2. In the present application, the addition amount of polyethylene glycol with different molecular weights is controlled so that the polyethylene glycol with different molecular weights can be entangled and connected with each other, so that a good strength adhesive film is formed after the hot melt adhesive is cured. Polytetrahydrofuran diol contains easily rotatable ether oxygen bonds, which introduce soft segments into the adhesive film. Too low an addition amount will affect the flexibility of the adhesive film, and too high an addition amount will easily affect the formability and strength of the adhesive film.

[0023] 3. The porous hollow fibers of polyacrylonitrile in the present application have a hollow structure and good mechanical properties, which can effectively improve the tensile strength of the film, thereby helping to improve the flexibility of the film. The nanocellulose whiskers have high strength and are entangled and overlapped with the porous hollow fibers of polyacrylonitrile, which can further provide the flexibility of the film. DETAILED DESCRIPTION

[0024] The present application is further described in detail below with reference to the embodiments. Preparation Example 1-11 of Polyacrylonitrile Porous Hollow Fiber

[0025] Preparation Example 1 The preparation method of polyacrylonitrile porous hollow fiber comprises the following steps: dissolving polyacrylonitrile and polyvinyl pyrrolidone in N, N-dimethylformamide to form a shell spinning solution with a polyacrylonitrile mass fraction of 10wt% and a polyvinyl pyrrolidone mass fraction of 10wt%, dissolving polyvinyl pyrrolidone in N, N-dimethylformamide to form a core spinning solution with a polyvinyl pyrrolidone mass fraction of 18wt%, coaxially electrospinning the core spinning solution and the shell spinning solution, wherein the shell spinning flow rate is 0.01mL / min, the core layer spinning flow rate is 0.01mL / min, the receiving distance is 14cm, the spinning voltage is 14kV, and a composite fiber is obtained; the composite fiber is heated at 55°C for 13h, then put into water, and shaken at 60°C for 3h.

[0026] Preparation Example 2 The preparation method of polyacrylonitrile porous hollow fiber comprises the following steps: dissolving polyacrylonitrile and polyvinyl pyrrolidone in N, N-dimethylformamide to form a shell spinning solution with a polyacrylonitrile mass fraction of 8wt% and a polyvinyl pyrrolidone mass fraction of 7wt%, dissolving polyvinyl pyrrolidone in N, N-dimethylformamide to form a core spinning solution with a polyvinyl pyrrolidone mass fraction of 16wt%, coaxially electrospinning the core spinning solution and the shell spinning solution, wherein the shell spinning flow rate is 0.011mL / min, the core layer spinning flow rate is 0.009mL / min, the receiving distance is 15cm, the spinning voltage is 14kV, and a composite fiber is obtained; the composite fiber is heated at 60°C for 12h, then put into water, and shaken at 55°C for 4h.

[0027] Preparation Example 3 The preparation method of polyacrylonitrile porous hollow fiber comprises the following steps: dissolving polyacrylonitrile and polyvinyl pyrrolidone in N, N-dimethylformamide to form a shell spinning solution with a polyacrylonitrile mass fraction of 12wt% and a polyvinyl pyrrolidone mass fraction of 13wt%, dissolving polyvinyl pyrrolidone in N, N-dimethylformamide to form a core spinning solution with a polyvinyl pyrrolidone mass fraction of 20wt%, coaxially electrospinning the core spinning solution and the shell spinning solution, wherein the shell spinning flow rate is 0.011mL / min, the core layer spinning flow rate is 0.012mL / min, the receiving distance is 16cm, the spinning voltage is 14kV, and a composite fiber is obtained; the composite fiber is heated at 60°C for 12h, then put into water, and shaken at 60°C for 3h.

[0028] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that in Preparation Example 4, the spinning flow rate of the core layer is 0.005 mL / min.

[0029] Preparation Example 5 The difference between Preparation Example 5 and Preparation Example 1 is that in Preparation Example 5, the spinning flow rate of the core layer is 0.017 mL / min.

[0030] Preparation Example 6 The difference between Preparation Example 6 and Preparation Example 1 is that in Preparation Example 6, the mass fraction of polyacrylonitrile in the shell spinning solution is 5wt%.

[0031] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 1 is that in Preparation Example 7, the mass fraction of polyacrylonitrile in the shell spinning solution is 18 wt %.

[0032] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 1 is that in Preparation Example 8, graphene is also added to the shell spinning solution, the added amount of graphene is 0.89wt% of polyacrylonitrile, and the graphene is dispersed in the shell spinning solution by ultrasound.

[0033] Preparation Example 9 The difference between Preparation Example 9 and Preparation Example 1 is that in Preparation Example 9, graphene is also added to the shell spinning solution, the added amount of graphene is 1.15wt% of polyacrylonitrile, and the graphene is dispersed in the shell spinning solution by ultrasound.

[0034] Preparation Example 10 The difference between Preparation Example 10 and Preparation Example 8 is that in Preparation Example 10, the added amount of graphene is 0.5 wt % of polyacrylonitrile.

[0035] Preparation Example 11 The difference between Preparation Example 11 and Preparation Example 8 is that in Preparation Example 11, the added amount of graphene is 1.65 wt % of polyacrylonitrile.

[0036] Example In the examples of the present application, the antioxidant is 2,4-dimethyl-6-tert-butylphenol, the tackifying resin is rosin resin, the defoaming agent is BYK-A555, and the nanocellulose whiskers are purchased from Zhongke Leiming (Beijing) Technology Co., Ltd.

[0037] Example 1 A low-temperature reactive hot-melt adhesive tape comprises the following raw materials in parts by weight: 75 kg of mixed polyol, 12 kg of diisocyanate, 3 kg of antioxidant, 3 kg of tackifying resin, 1.8 kg of toughening agent, and 0.2 kg of defoaming agent, wherein the mixed polyol comprises polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200, and polytetrahydrofuran diol in a mass ratio of 0.3:0.3:0.25:3.08, the toughening agent comprises polyacrylonitrile porous hollow fiber and nanocellulose whisker in a mass ratio of 1.56:0.75, and the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 1.

[0038] The preparation method of the above-mentioned low-temperature reactive hot-melt tape comprises the following steps: stirring and mixing polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol to obtain a mixed polyol, mixing the mixed polyol, a tackifying resin, an antioxidant and a defoaming agent, and vacuum dehydrating for 1.8 hours at 120°C; adding a toughening agent to the above-mentioned mixture, stirring and dispersing for 1.5 hours at a speed of 2000r / min and a temperature of 130°C, adding diisocyanate, maintaining the reaction temperature at 130°C, stirring for 2.5 hours, extruding and molding, cooling, and obtaining a low-temperature reactive hot-melt tape.

[0039] Example 2 A low-temperature reactive hot-melt adhesive tape comprises the following raw materials in parts by weight: 65 kg of mixed polyols, 7 kg of diisocyanate, 2 kg of antioxidant, 2 kg of tackifying resin, 1.3 kg of toughening agent, and 0.1 kg of defoaming agent, wherein the mixed polyols comprise polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200, and polytetrahydrofuran diol in a mass ratio of 0.28:0.27:0.23:2.82, the toughening agent comprises polyacrylonitrile porous hollow fibers and nanocellulose whiskers in a mass ratio of 1.25:0.67, and the polyacrylonitrile porous hollow fibers are the polyacrylonitrile porous hollow fibers prepared in Preparation Example 1.

[0040] The preparation method of the above-mentioned low-temperature reactive hot-melt tape comprises the following steps: stirring and mixing polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol to obtain a mixed polyol, mixing the mixed polyol, a tackifying resin, an antioxidant and a defoaming agent, and vacuum dehydrating for 2 hours at 100°C; adding a toughening agent to the above-mentioned mixture, stirring and dispersing for 2 hours at a speed of 1500r / min and a temperature of 120°C, adding diisocyanate, maintaining the reaction temperature at 120°C, stirring for 3 hours, extruding and molding, and cooling to obtain a low-temperature reactive hot-melt tape.

[0041] Example 3 A low-temperature reactive hot-melt adhesive tape comprises the following raw materials in parts by weight: 85 kg of mixed polyols, 18 kg of diisocyanate, 5 kg of antioxidant, 5 kg of tackifying resin, 2.7 kg of toughening agent, and 0.4 kg of defoaming agent, wherein the mixed polyols comprise polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200, and polytetrahydrofuran diol in a mass ratio of 0.32:0.33:0.26:3.16, the toughening agent comprises polyacrylonitrile porous hollow fibers and nanocellulose whiskers in a mass ratio of 1.67:0.98, and the polyacrylonitrile porous hollow fibers are the polyacrylonitrile porous hollow fibers prepared in Preparation Example 1.

[0042] The preparation method of the low-temperature reactive hot-melt tape comprises the following steps: polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol are stirred and mixed to obtain a mixed polyol; the mixed polyol, a tackifying resin, an antioxidant and a defoaming agent are mixed, and vacuum dehydration is performed at 130°C for 1.5-2h; a toughening agent is added to the mixture, and after stirring and dispersing for 1h at a speed of 3200r / min and a temperature of 145°C, a diisocyanate is added, the reaction temperature is maintained at 135°C, stirring for 2h, extruding and molding, and cooling to obtain a low-temperature reactive hot-melt tape.

[0043] Example 4 The difference between Example 4 and Example 1 is that the mass ratio of the polyacrylonitrile porous hollow fiber to the nanocellulose whisker is 1.25:0.46.

[0044] Example 5 The difference between Example 5 and Example 1 is that the mass ratio of the polyacrylonitrile porous hollow fiber to the nanocellulose whiskers is 1.25:1.23.

[0045] Example 6 The difference between Example 6 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 4.

[0046] Example 7 The difference between Example 7 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 5.

[0047] Example 8 The difference between Example 8 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 6.

[0048] Example 9 The difference between Example 9 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 7.

[0049] Example 10 The difference between Example 10 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 8.

[0050] Embodiment 11 The difference between Example 11 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 9.

[0051] Example 12 The difference between Example 12 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 10.

[0052] Embodiment 13 The difference between Example 13 and Example 1 is that the polyacrylonitrile porous hollow fiber is the polyacrylonitrile porous hollow fiber prepared in Preparation Example 11.

[0053] Embodiment 14 The difference between Example 14 and Example 1 is that the nanocellulose whiskers are treated as follows: the nanocellulose whiskers are dispersed in 50 mL of glacial acetic acid to form a suspension with a nanocellulose whisker mass fraction of 12 wt%, and 60 mL of a mixture of sulfuric acid, glacial acetic acid and acetic anhydride is added dropwise while stirring, the amount of sulfuric acid added is 0.6 wt % of the nanocellulose whiskers, the mass ratio of acetic anhydride to nanocellulose whiskers is 2:8, the temperature is raised to 45°C after the addition, the reaction is carried out for 30 minutes, the suspension is washed with ethanol and acetone, and the suspension is filtered.

[0054] Embodiment 15 The difference between Example 15 and Example 1 is that the nanocellulose whiskers are treated as follows: the nanocellulose whiskers are dispersed in 50 mL of glacial acetic acid to form a suspension with a nanocellulose whisker mass fraction of 10 wt%, and 55 mL of a mixture of sulfuric acid, glacial acetic acid and acetic anhydride is added dropwise while stirring, the amount of sulfuric acid added is 0.8 wt % of the nanocellulose whiskers, and the mass ratio of acetic anhydride to nanocellulose whiskers is 2.2:7.9. After the addition, the temperature is raised to 40°C, the reaction is carried out for 35 minutes, the mixture is washed with ethanol and acetone, and filtered.

[0055] Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the amount of toughening agent added is 0.5 kg.

[0056] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, the amount of toughening agent added is 3.5 kg.

[0057] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, an equal amount of polyethylene glycol 8000 is used instead of the mixed polyol.

[0058] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that, in Comparative Example 4, polytetrahydrofuran diol is not added.

[0059] Performance testing According to the raw materials and preparation methods of Examples 1-15 and Comparative Examples 1-4, hot melt tapes were prepared and tested. The softening point of the hot melt adhesive was tested with reference to GBT15332-1994-Ring and Ball Method for Determination of Softening Point of Hot Melt Adhesives. The 90° peel strength of the hot melt adhesive at 30°C was determined using a tensile testing machine with reference to ASTMD 1002—2019 standard. The tensile strength of the adhesive film after curing the hot melt adhesive was determined with reference to GB / T528—2009, and the results are recorded in Table 1.

[0060] Table 1 Performance test of hot melt adhesive film project Softening point / ℃ Peel strength / (N / cm) Tensile strength / MPa Example 1 54 6.59 26.98 Example 2 55 6.23 25.99 Example 3 53 6.23 26.57 Example 4 55 5.21 23.26 Example 5 56 5.13 23.13 Example 6 54 5.34 22.61 Example 7 55 5.24 23.01 Example 8 53 5.23 21.32 Example 9 55 5.21 22.01 Example 10 56 5.98 29.15 Embodiment 11 53 5.87 28.98 Example 12 54 5.46 26.59 Embodiment 13 56 5.57 27.01 Embodiment 14 53 5.92 28.68 Embodiment 15 55 5.88 28.95 Comparative Example 1 52 5.51 26.26 Comparative Example 2 53 5.62 27.21 Comparative Example 3 46 ———— ———— Comparative Example 4 45 ———— ———— It can be seen from Examples 1-3, Comparative Examples 1-4 and Table 1 that the hot melt tapes prepared in Examples 1-3 have a lower softening point, good peel strength and tensile strength, so that the hot melt tapes can be used at a lower temperature, reducing the effect of temperature on the bonded objects. The mixed polyols react with diisocyanates to prepare thermoplastic polyurethane. The mixed polyols include polytetramethylene glycol and polyethanol of various molecular weights. Polyethylene glycols of different molecular weights can make the hot melt adhesive solidify to form an adhesive film with good strength. Polytetramethylene glycol contains easily rotatable ether oxygen bonds, which can destroy the regularity of polyethylene glycol, thereby reducing the softening point of the hot melt adhesive, improving the flexibility of the adhesive film, and making it have higher peel strength and tensile strength.

[0061] Compared with Examples 1-3, the tensile strength of Comparative Example 1-2 is reduced, indicating that the amount of toughening agent added has an effect on the tensile strength of the film. The toughening agent is a composite of polyacrylonitrile porous hollow fibers and nanocellulose whiskers. The polyacrylonitrile porous hollow fibers have good mechanical properties, and the hollow structure can provide deformation space for its force, further improving its tensile strength. The nanocellulose whiskers have higher whiskers and have a bud-like structure, which are intertwined and overlapped with the polyacrylonitrile porous hollow fibers to form a three-dimensional structure, which can further improve the flexibility of the film. The softening point of Comparative Example 3-4 is reduced compared with Examples 1-3, but the hot melt adhesive prepared in Comparative Example 3-4 is not easy to form a film, the regularity of polyvinyl alcohol is good, and the brittleness of the prepared polyurethane is high, and it is not possible to form a good film.

[0062] Compared with Examples 1-3, the tensile strength of the film formed by the hot melt adhesive in Example 4-5 is reduced. In Example 4-5, the mass ratio of the polyacrylonitrile porous hollow fiber and the nanocellulose whisker in the toughening agent is changed, indicating that there is a synergistic effect between the polyacrylonitrile porous hollow fiber and the nanocellulose whisker. The nanocellulose whisker has a branch-like structure and can disperse energy. The nanocellulose whisker is used together with the polyacrylonitrile porous hollow fiber, so that it can quickly disperse and deform when subjected to force, maintain its physical structure, and is beneficial to improving the tensile strength of the film.

[0063] Compared with Examples 1-3, the tensile strength of the adhesive film formed by the hot melt adhesive in Examples 6-7 decreases. During the preparation of the polyacrylonitrile porous hollow fiber used in Examples 6-7, the spinning flow rate of the core layer was changed. The spinning flow rate of the core layer affected the inner diameter of the polyacrylonitrile porous hollow fiber. The spinning flow rate of the core layer decreased, the hollow structure thereof almost disappeared, the tensile resistance decreased, and the tensile strength of the adhesive film decreased. The spinning flow rate of the core layer increased, and the inner diameter of the polyacrylonitrile porous hollow fiber was too large, which made its structure loose, reduced mechanical strength, and reduced the tensile strength of the adhesive film.

[0064] Compared with Examples 1-3, the tensile strength of the adhesive film formed by the hot melt adhesive in Examples 8-9 decreases. During the preparation of the polyacrylonitrile porous hollow fibers used in Examples 8-9, the mass fraction of polyacrylonitrile in the shell spinning solution was changed. The mass fraction of polyacrylonitrile in the shell spinning solution affected the tube wall condition of the polyacrylonitrile porous hollow fibers. When the mass fraction of polyacrylonitrile decreased, its porosity increased, which reduced the mechanical strength and thus reduced the tensile strength of the adhesive film. When the mass fraction of polyacrylonitrile increased, the porosity decreased, the deformation space decreased, its tensile resistance decreased, and the tensile strength of the adhesive film decreased.

[0065] Compared with Examples 1-3, the tensile strength of the adhesive film formed by the hot melt adhesive in Examples 10-11 is improved. When preparing the polyacrylonitrile porous hollow fibers used in Examples 10-11, graphene is added to the shell spinning solution. Graphene has good mechanical properties and strength. Adding graphene to the shell spinning solution allows graphene to be incorporated into the tube wall of the polyacrylonitrile porous hollow fiber, effectively improving the mechanical strength and tensile strength of the polyacrylonitrile porous hollow fiber, thereby improving the tensile strength of the adhesive film.

[0066] Compared with Examples 10-11, the tensile strength of the adhesive film formed by the hot melt adhesive in Examples 12-13 decreases. During the preparation of the polyacrylonitrile porous hollow fibers used in Examples 12-13, the amount of graphene added was changed. When the amount of graphene added was reduced, the reinforcing effect of the graphene on the polyacrylonitrile porous hollow fibers was weakened, resulting in a decrease in the tensile strength of the adhesive film. When the amount of graphene added was increased, the graphene was prone to agglomeration and uneven dispersion, and the spinning process was not smooth. The structure and strength of the formed polyacrylonitrile porous hollow fibers were affected, resulting in a decrease in the tensile strength of the adhesive film.

[0067] Compared with Examples 1-3, the tensile strength of the adhesive film formed by the hot melt adhesive in Examples 14-15 is improved. In Examples 14-15, the nanocellulose whiskers are subjected to acetic acid esterification treatment. The acetic acid esterification treatment of the nanocellulose whiskers can effectively improve the dispersibility of the nanocellulose whiskers, making the nanocellulose whiskers evenly dispersed, and interact with the polyacrylonitrile porous hollow fibers to reinforce the adhesive film and improve its tensile strength.

[0068] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A low temperature reactive hot melt adhesive tape, characterized in that: The invention comprises the following raw materials in parts by weight: 65-85 parts of mixed polyol, 7-18 parts of diisocyanate, 2-5 parts of antioxidant, 2-5 parts of tackifying resin, 1.3-2.7 parts of toughening agent and 0.1-0.4 parts of defoaming agent, wherein the mixed polyol comprises polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetramethylene glycol.

2. A low temperature reactive hot melt adhesive tape according to claim 1, characterized in that: In the mixed polyol, the mass ratio of polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol is (0.28-0.32):(0.27-0.33):(0.23-0.26):(2.82-3.16).

3. A low temperature reactive hot melt adhesive tape according to claim 1, characterized in that: The toughening agents are polyacrylonitrile porous hollow fibers and nano cellulose whiskers.

4. A low temperature reactive hot melt adhesive tape according to claim 3, characterized in that: The mass ratio of the polyacrylonitrile porous hollow fiber to the nanocellulose whiskers is (1.25-1.67):(0.67-0.98).

5. The low temperature reactive hot melt adhesive tape according to claim 3, characterized in that: The preparation method of the polyacrylonitrile porous hollow fiber comprises the following steps: dissolving polyacrylonitrile and polyvinyl pyrrolidone in N,N-dimethylformamide to form a shell spinning solution; dissolving polyvinyl pyrrolidone in N,N-dimethylformamide to form a core spinning solution; coaxially electrospinning the core spinning solution and the shell spinning solution to obtain a composite fiber; heating the composite fiber at 55-60°C for 12-13h, placing the composite fiber in water, and shaking at 55-60°C for 3-4h.

6. A low temperature reactive hot melt adhesive tape according to claim 5, characterized in that: Graphene is also added to the shell spinning solution, and the added amount of graphene is 0.89-1.16wt% of the polyacrylonitrile.

7. The low temperature reactive hot melt adhesive tape according to claim 3, characterized in that: The nanocellulose whiskers are treated as follows: the nanocellulose whiskers are dispersed in acetic acid to form a suspension, a mixture of sulfuric acid, acetic acid and acetic anhydride is added dropwise while stirring, the temperature is raised to 40-45° C. after the addition, the reaction is carried out for 30-35 minutes, the nanocellulose whiskers are washed with ethanol and acetone, and the suspension is filtered.

8. The method for preparing a low-temperature reactive hot-melt adhesive tape according to any one of claims 1 to 7, characterized in that: The following steps are involved: Polyethylene glycol 8000, polyethylene glycol 600, polyethylene glycol 200 and polytetrahydrofuran diol are stirred and mixed to obtain a mixed polyol, the mixed polyol, a tackifying resin, an antioxidant and a defoaming agent are mixed, and vacuum dehydration is performed at 100-130° C. for 1.5-2 hours; a toughening agent is added to the mixture, and the mixture is stirred and dispersed at a speed of 1500-3200 r / min and a temperature of 120-145° C. for 1-2 hours, and then diisocyanate is added, the reaction temperature is maintained at 120-135° C., and the mixture is stirred for 2-3 hours, extruded and cooled to obtain a low-temperature reactive hot melt adhesive tape.